Comparative effectiveness of hybrid and laparoscopic techniques for repairing complex incisional ventral hernias: a systematic review and meta-analysis - Quan Wu; Weijie Ma; Qianqian Wang; Yaqi Liu; Yaokai Xu (BMC Surgery, 2023)
Abstract Background The recently developed Hybrid Hernia Repair technique (HHR), an adaptation of the laparoscopic method, has been proposed as a potential alternative for the treatment of complex Incisional Ventral Hernias (IVH). While single-arm studies have reported promising outcomes, a comprehensive meta-analysis affirming these benefits is lacking. This meta-analysis aims to compare the clinical outcomes of HHR and Laparoscopic Hernia Repair (LHR) in the management of IVH. Methods An exhaustive search of the literature was conducted, targeting publications in both English and Chinese that compare HHR and LHR up to March 31, 2023. The primary outcomes examined were operation time, blood loss, and intestinal injury. Secondary outcomes included rates of seroma, wound infection, post-operative acute/chronic pain, recurrence, and mesh bulging. The RevMan 5.0 software facilitated the statistical meta-analysis. Results The final analysis incorporated data from 14 studies, encompassing a total of 1158 patients, with 555 undergoing HHR and 603 treated with LHR. Follow-up data, ranging from 12 to 88 months, were available in 12 out of the 14 identified studies. The HHR method was associated with a significantly lower risk of seroma (OR = 0.29, P = 0.0004), but a higher risk of wound infection (OR = 2.10, P = 0.04). No significant differences were observed between the two techniques regarding operation time, blood loss, intestinal injury, intestinal obstruction, post-operative pain, mesh bulging, and recurrence. Conclusions The HHR technique did not demonstrate a clear advantage over LHR in reducing surgical complications, apart from a lower incidence of postoperative seroma. Surgeons with substantial expertise may choose to avoid incidental conversion or intentional hybrid procedures. Further research is needed to clarify the optimal surgical approach for IVH.